2021
DOI: 10.3390/ijerph18105176
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Underweight, Overweight and Obesity in School-Aged Children in the Urban Area of the Northwestern Part of Romania

Abstract: Introduction: During the last three decades, there has been an excess weight epidemic due to changes in nutrition and lifestyle. Few data on the prevalence of overweight and obesity in children in Romania were published, without a single study representative at the national level. There are reports on the higher level of overweight and obesity in urban areas compared to rural ones. This study aimed to estimate the prevalence of underweight, overweight, obesity and severe obesity in children enrolled in schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 43 publications
(92 reference statements)
1
22
0
Order By: Relevance
“…Our study showed that 31.6% of the participating children were overweight or obese. Another study performed in 2016 on a large representative sample from Northwestern Romania among 7–18 year old children showed a prevalence of overweight and obesity of about 30% [ 50 ]. In addition, a small percentage of children recruited in our study were underweight (7.4%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed that 31.6% of the participating children were overweight or obese. Another study performed in 2016 on a large representative sample from Northwestern Romania among 7–18 year old children showed a prevalence of overweight and obesity of about 30% [ 50 ]. In addition, a small percentage of children recruited in our study were underweight (7.4%).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the studies published between 2006 and 2015 showed that 25% of youth aged 6–19 years old were overweight or obese [ 49 ]. A recent study showed that prevalence of overweight and obesity among children and adolescents aged 7–18 years old from the western part of the country was 30% and it was highest among pre-pubertal children and boys [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity in children is a rapidly growing community health issue that has reached epidemic proportions around the world. From 1975 (4%) to 2016, the global prevalence of obesity in children and adolescents tripled (over 18%) [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…Body mass index (BMI) can be used to define obesity. "BMI = weight in kg/(height in meters) [2]." The criterion for obesity is BMI ≥95…”
Section: Introductionmentioning
confidence: 99%